Renal tubular dysfunction and urinary zinc excretion in breast cancer patients treated with anthracycline-based combination chemotherapy - Králícková, P; Melichar, B; Malír, F; Roubal, T (Journal of experimental & clinical cancer research, 2004)
The survival of breast cancer patients has significantly improved through the treatment with anthracyclines. Although anthracyclines are known to produce renal disease in experimental animals, little is known about the toxicity of anthracyclines at clinically relevant doses in humans. In a previous study on cancer patients we have observed an increase in the urinary activity of N-acetyl-beta-D-glucosaminidase (NAG), an indicator of renal tubular cell dysfunction that was accompanied by increased urinary zinc loss. Because an increase in NAG activity was reported after the treatment with anthracyclines, we hypothesized that an increase in urinary NAG activity in breast cancer patients treated with anthracycline-based regimens will be accompanied by hyperzincuria and hypozincemia. Urinary and serum zinc, urinary NAG and serum creatinine were examined during chemotherapy in 26 breast cancer patients treated with anthracycline-based chemotherapy. A trend for increased NAG activity, as compared to baseline, was observed throughout the first 4 cycles of treatment. NAG activity was significantly elevated compared to pretreatment levels one week after the first, third and fourth dose of chemotherapy. Serum creatinine concentrations decreased significantly after the second cycle of therapy. On the other hand, urinary and serum zinc levels did not change significantly during the treatment. In conclusion, our data confirm the presence of mild renal tubular cell dysfunction in breast cancer patients treated with doxorubicin-based chemotherapy. Increased urinary NAG is accompanied by a decrease in serum creatinine which is consistent with hyperfiltration. These changes are not associated with abnormalities of renal zinc handling or a decrease in serum zinc concentrations.
Keywords: acetylglukosaminidasa; doxorubicin; kreatin; Kidney Diseases; protinádorová antibiotika; Anthracyclines; kombinovaná farmakoterapie; Adult; Kidney; Acetylglucosaminidase; Aged; dospělí; nádory prsu; senioři; nemoci ledvin; Drug Therapy, Combination; Time Factors; Creatine; lidé; ženské pohlaví; Breast Neoplasms; Humans; ledviny; Antibiotics, Antineoplastic; časové faktory; antracykliny; zinek; Female; Zinc; lidé středního věku; Doxorubicin; Middle Aged